Work Expectations and Self-Efficacy on Intention to Apply: Does Personal Motivation Play a Role? - Widjanarko, Muhammad Akhdan; Fahreza Sani, Ahmad Firza (MEC-J (Management and Economics Journal), 2025)
This study aims to examine the influence of job expectations and self-efficacy on the intention to apply for jobs among Generation Z, with personal motivation as a mediating variable. The research is motivated by the high unemployment rate, which presents a significant challenge for young graduates, especially those without work experience. Furthermore, the gap between job expectations and actual conditions often hinders young graduates from entering the workforce. Data were collected through the distribution of questionnaires to Generation Z individuals in Malang City. The population in this study includes Generation Z from five districts in Malang City: Blimbing, Kedungkandang, Klojen, Lowokwaru, and Sukun. Purposive sampling was used, and data were analyzed using the Partial Least Squares (PLS) method with the SmartPLS 4.0 software. The results indicate that job expectations have a positive and significant effect on the intention to apply, both directly and indirectly through personal motivation. Meanwhile, self-efficacy does not directly influence the intention to apply but has a significant indirect effect through personal motivation. These findings highlight the crucial mediating role of personal motivation in the relationship between self-efficacy and job expectations on the intention to apply. Therefore, companies and career development practitioners are advised not only to focus on boosting self-confidence but also to strengthen internal motivation and address the job expectations of Generation Z to enhance their intention to apply for jobs.